Effect of the activator impurity on the scintillation yield in alkali‐halide crystals. Issue 2 (10th October 2014) - Gektin, A.; Gridin, S.; Vasyukov, S.; Vasil'ev, A.; Belsky, A.; Shiran, N.
<x xml:space="preserve">Abstract</x> The influence of different activator impurities on the scintillation yield of alkali halides has been investigated as a function of temperature. Luminescence spectra of pure and activated CsI and NaI scintillation crystals were measured under X‐ray and VUV excitation at temperatures from 10 to 300 K. In indium‐ and thallium‐doped crystals activator centers can capture electrons. Along with self‐trapping of holes at low temperatures, electron capture by the dopant results in energy storage. This leads to a significant decrease of luminescence yield. In Eu‐doped NaI and CsI crystals activator centers capture a hole first. In this way, at low temperatures electrons recombine either with self‐trapped holes (yielding STE emission), or with holes trapped by the activator (giving rise to Eu emission band). No energy loss at low temperature is evident in CsI:Eu and NaI:Eu crystals.